1991
DOI: 10.1111/j.1471-4159.1991.tb11405.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Protein Tyrosine Phosphorylation in Alzheimer's Disease

Abstract: The activity of protein tyrosine kinase was determined in extracts from Alzheimer's disease brains and age- and postmortem time-matched control brains at autopsy using the synthetic peptide substrate poly(Glu4Tyr1). The specific activity of protein tyrosine kinases in the particulate fraction decreased roughly twofold (p less than 0.02) in Alzheimer's disease frontal cortex relative to unaffected control cortex. Cytosolic protein tyrosine kinase activity in Alzheimer's disease tissue was not significantly diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

1992
1992
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 49 publications
2
16
0
3
Order By: Relevance
“…Neuritic plaques and dystrophic neurites in AD brains contain a large amount of phosphotyrosine (pTyr) (Masliah et al, 1991; Shapiro et al, 1991), and cultured cells exposed to Aβ show higher levels of pTyr proteins (Bamberger et al, 2003; Grace and Busciglio, 2003; Matrone et al, 2009). Additionally an abnormally enhanced APP phosphorylation on Tyr residues has been previously reported in AD brain (Russo et al, 2001; Rebelo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Neuritic plaques and dystrophic neurites in AD brains contain a large amount of phosphotyrosine (pTyr) (Masliah et al, 1991; Shapiro et al, 1991), and cultured cells exposed to Aβ show higher levels of pTyr proteins (Bamberger et al, 2003; Grace and Busciglio, 2003; Matrone et al, 2009). Additionally an abnormally enhanced APP phosphorylation on Tyr residues has been previously reported in AD brain (Russo et al, 2001; Rebelo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Our data now suggest that this could result in increased activation of SFK in the course of neuropathogenesis. It has been reported that AD brains have an increase in tyrosine phosphorylated proteins (Shapiro et al, 1991) as well as altered localizations of Fyn and Src (Ho et al, 2005;Shirazi and Wood, 1993). An increase in SFK activity would impact on synaptic transmission and plasticity (reviewed by Kalia et al, 2004) and evidence for the role of Fyn in synaptotoxicity in AD has been obtained using mouse models (Chin et al, 2005; Chin et al, 2004).…”
Section: Journal Of Cell Sciencementioning
confidence: 99%
“…In addition, several other studies have suggested a role for tyrosine phosphorylation in AD. AD brains showed an increase in phosphotyrosine-containing proteins (Shapiro et al, 1991), and cultured cells exposed to A␤ contained higher levels of tyrosine phosphorylated proteins (Luo et al, 1995;Moore et al, 2002;Bamberger et al, 2003;Grace and Busciglio, 2003). Tyrosine phosphorylation of paxillin (Grace and Busciglio, 2003), tau (Williamson et al, 2002), and several protein kinases, including focal adhesion kinase (Zhang et al, 1994;Williamson et al, 2002), MAP kinase (Sato et al, 1997), and phosphatidylinositol 3-kinase (Luo et al, 1996), increase in the presence of A␤.…”
Section: Introductionmentioning
confidence: 99%